Analisis Pengaruh Brand Image, Kualitas Produk dan Harga Terhadap Keputusan Pembelian Skincare The Originote - Bachtiar, Danis Imam; Bachtiar, Firman; Teguh Supriyanto, Wahyuningsih (Jurnal Metaverse ADPERTISI, 2024)
This study aims to test and analyze the effect of Brand image, product quality and price on purchasing decisions for The Originote skincare. This study uses primary data by distributing questionnaires. The sample used was quota sampling of 100 respondents who used The Originote skincare. The data obtained was processed using SPSS version 22. The data analysis technique uses validity test, reliability test, multiple linear test, F test, T test and coefficient of determination. The results showed that (1) Brand image (X1) partially influenced the decision to purchase The Originote skincare with the t test result of 2.243. (2) Product quality (X2) partially influenced the decision to purchase The Originote skincare with the t test result of 2.592. (3) Price (X3) partially has no effect on purchasing decisions for The Originote skincare with the t test result of 1.078. (4) Brand image, product quality and price silmutan affect the purchasing decision of The Originote skincare. For R square of 0.410 which means that 41% of purchasing decision variables can be explained by Brand image, product quality and price variables, while 59% is explained by other variables not used in this study, namely location, promotion and convenience.